An assessment of the impacts of community development initiatives in Awgbu Town in Anambra State, Nigeria - Chukwudi, Celestina Ekene Nwankiti; Owoh, Emeka Emmanuel (Research Journal in Advanced Humanities, 2024)
This research evaluates how the Awgbu community has contributed to the general development of Anambra State, how it has benefited from state government efforts, and how it has responded to demands and initiatives from the government between 2015 and 2023. Community Development (CD), Social Capital, and the Diffusion of Innovations theories are the underpinning theoretical framework of analysis used for the study. The research design used in this paper was a descriptive survey, with data collected from primary and secondary sources. Since the study was intended for the entire population of Awgbu town, Slovin’s sample determination formula and the purposive random sampling technique were employed. Specifically, a sample size of 400 respondents was targeted, and 286 returned questionnaires were used for data analysis. The gathered data were displayed on the Logical Data Framework (LDF) and subjected to a quantitative statistical data analysis technique that involved weighted mean and frequency tables. The results show that the Awgbu community has significantly influenced Anambra State’s growth. Through its participation in the Choose Your Project Initiative (CYPI), the community has actively reacted to requests from the government. Nonetheless, the research discovers that, among other things, inadequate money, oversight, and leadership crises impede the community’s advancement.